Impact of on-the-job Training on Employee Performance (A Case Study of Microfinance Banks in District Khairpur) - Muneer, Dr. Syed; Shah, Turab Ali; Abbas, Syed Hassan (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
The study was conducted to examine the impact of on-the- job training on employee performance by using a questionnaire for collecting responses from the sample to check the above relation through SPSS 16. Data reduction technique was used to form the factors from number of variables and then linear regression was applied by putting employee performance as a dependent variable and training as a independent variable. Study concluded that 50% of employee performance depends on- the- job training.Â 